2020
DOI: 10.1093/gerona/glz295
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Frailty and Cognitive Decline Among Older Mexican Americans

Abstract: Background Progressive physical frailty and cognitive decline in older adults is associated with increased risk of falls, disability, institutionalization, and mortality; however, there is considerable heterogeneity in progression over time. We identified heterogeneous frailty and cognitive decline trajectory groups and examined the specific contribution of health conditions to these trajectories among older Mexican origin adults. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 47 publications
3
35
1
1
Order By: Relevance
“…For residents who experienced “Worsening Frailty” or were “Consistently Frail”, the majority followed the “Consistently Severe Cognitive Impairment” trajectory. These findings were similar to a study in older Mexican American community-dwelling adults [ 55 ]. However, due to modeling convergence constraints, we were not able to identify relevant resident characteristics associated with both sets of trajectories.…”
Section: Discussionsupporting
confidence: 91%
“…For residents who experienced “Worsening Frailty” or were “Consistently Frail”, the majority followed the “Consistently Severe Cognitive Impairment” trajectory. These findings were similar to a study in older Mexican American community-dwelling adults [ 55 ]. However, due to modeling convergence constraints, we were not able to identify relevant resident characteristics associated with both sets of trajectories.…”
Section: Discussionsupporting
confidence: 91%
“…Our study identified three distinct types of frailty trajectories: “Non-frail”, “Pre-frail to frail” and “Frail to severely frail”. Similar to our findings, Howrey et al identified three groups of frailty: “non-frail”, “moderate progressive frailty” and “progressive high frailty” among older Mexican Americans [ 28 ]. However, this study used the survey wave as the underlying time scale, which is not suitable for analyzing the trajectory of age-related phenotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have also identified distinct frailty trajectories over age, that is, clusters of individuals that follow a similar growth pattern ( 8–10 ). Low education has been associated with likelihood of being in the high frailty trajectory ( 8 , 10 ) and associate with a steeper rate of change in frailty ( 11 ). However, studies assessing the factors that influence changes in frailty over a long period of time (decades) and use multiple, repeated measurements in both frailty and the risk factors are lacking.…”
mentioning
confidence: 99%